Above-the-Line Promotion and Hotel Guests' Stay Decisions at Pangeran City Hotel Padang - Santika Oktavia Fani; Feri Ferdian (Journal of Multidimensional Management, 2026)
Pangeran City Hotel Padang used a mix of broad-reach and digital promotional channels but experienced difficulty maintaining guest volume during periods when stronger demand was expected, creating a need to assess whether promotional communication was associated with hotel selection. This study examines the relationship between above-the-line promotion and guests' decisions to stay. A quantitative cross-sectional causal-associative survey was conducted during April-May 2023 with 100 hotel guests selected through purposive sampling. Data were collected using a five-point Likert-scale questionnaire and analyzed with partial least squares structural equation modeling (PLS-SEM) in SmartPLS 4. The final measurement model retained 19 promotion indicators and 27 stay-decision indicators. Outer loadings ranged from 0.721 to 0.849 and from 0.683 to 0.880, respectively; Cronbach's alpha values were 0.967 and 0.981, composite reliability values were 0.970 and 0.982, and HTMT was 0.731. Above-the-line promotion accounted for 51.8% of the variance in stay decision (R² = 0.518). The structural path was positive and significant (β = 0.729, t = 9.952, p < 0.001). The findings indicate that visible, credible, and decision-relevant promotion is positively associated with guests' hotel choice, while the distinction between traditional mass-media promotion and digital channels should be made more explicit in future measurement.